Exposures and associations with clinical phenotypes in hypersensitivity pneumonitis: A scoping review. (August 2021) - Barnes, Hayley; Lu, Jesse; Glaspole, Ian; Collard, Harold R.; Johannson, Kerri A.
Abstract: Antigen identification is important for establishing a confident diagnosis of hypersensitivity pneumonitis (HP). There are no systematically curated lists of HP-associated exposures that inform clinical relevance or disease phenotype. We sought to systematically identify all reported causes of HP in the literature and evaluate their clinical relevance. A scoping review was performed to identify all publications describing HP cases and their associated exposures (even if unknown) from Jan 1990–June 2020. Frequencies of exposures and meta-analysis of proportions for registry-based studies were determined for specific exposure categories, and associations with fibrotic and non-fibrotic HP were assessed. 24, 138 publications were identified, with 967 publications included in the final analysis, representing 62 unique exposures associated with HP. Certain exposures were more frequently reported than others, including birds (comprising 32% of HP cases in registry-based studies) and mould (17% registry study HP cases). Antigen-indeterminate HP comprised 15–24% of registry-based studies. Limited data found contaminated metal-working fluids, isocyanate exposure, and hot tub lung were rarely associated with fibrotic features, whereas antigen-indeterminate HP cases were more frequently associated with fibrosis. There was heterogeneity in HP case definition and how causative exposures were identified. We identified 62 unique exposures associated with HP, with specific exposures associated with clinical phenotypes. These data may inform clinical assessment and the development of questionnaires to identify antigens in the diagnostic evaluation of suspected HP. Open sciences framework registration: osf.io/4aq5m. Highlights: This scoping review describing exposures associated with hypersensitivity pneumonitis (HP) identified 62 unique exposures. Birds and mould were the most frequently reported exposures, accounting for 32% and 17% of HP cases in registry-based studies, respectively. Antigen-indeterminate HP comprised 15-24% of patients in registry-based studies. Limited data found MWF, isocyanates, and hot tub lung were rarely; and antigen-indeterminate HP more frequently associated with fibrotic HP. These data may inform clinical assessment and development of questionnaires to identify exposures in the diagnostic evaluation of suspected HP.